ALTERNATIVE ASSESSMENT IN SECOND LANGUAGE TEACHING - Nozima Rakhmatillayeva Nig‘matilla qizi (Western European Studies, 2025)
Assessment plays a central role in second language teaching, as it shapes pedagogical decisions, learner motivation, and the overall direction of language development. For decades, traditional assessment methods—such as standardized tests, discrete grammar exercises, and high-stakes final examinations—have dominated language classrooms. However, these approaches provide only a fragmented picture of learners’ language proficiency and often fail to capture communicative competence, strategic abilities, and the capacity to use language in real-life contexts. As a result, educators and researchers have increasingly turned to alternative assessment, which aims to provide a more holistic, learnercentered, and contextually meaningful evaluation of language competence.
Keywords: Alternative assessment; second language teaching; assessment for learning